Optical fiber sensors: review of technology and applications - Mahmoud M. A. Eid (Institute of Advanced Engineering and Science, 2022)
There is a huge increase in the usage of optical fiber sensors in various fields, especially the field of communications, as these sensors have been employed in a promising industry, namely, the internet of things. This industry is witnessing a growing demand for more sensors as well as employing them in new applications, and there is an urgent need to invent new sensors to meet our requirements in providing more time, luxury, and effort with the highest quality and the best possible performance. But there is now a lot of information about optical sensors as well as many classifications and applications. There are also some developments in a scientific research yard. The main objective of this paper is to introduce short, effective, and concentrated points in optical fiber sensors such as a brief historical background, their structure, and their different operation principles, different classifications for these sensors according to different categories, and finally advantages of fiber optical sensors compared to traditional electronic sensors. I hope this content will be very useful to anyone interested in these types of sensors. This review is done with particular assurance on the recently published information.